In ΔABC, prove that
.
Answers
Answered by
1
Solution :
i ) 1/r - 1/r1
= S/∆-(S-a)/∆
= (S-S+a)/∆
= a/∆
ii ) 1/r - 1/r²
= S/∆ - ( S - b )/∆
= ( S - S + b )/∆
= b/∆
iii ) 1/r - 1/r3
= S/∆ - ( S - c )/∆
= ( S - S + c )/∆
= c/∆
Now ,
LHS = (1/r-1/r1)(1/r-1/r2)(1/r-1/r3)
= ( a/∆ ) ( b/∆ ) ( c/∆ )
= ( abc )/∆³
= ( 4R * ∆ )/∆³
= 4R/∆²
= ( 4R )/( rs )² [ Since , ∆ = rs ]
= ( 4R )/( r²s² )
= RHS
•••••
i ) 1/r - 1/r1
= S/∆-(S-a)/∆
= (S-S+a)/∆
= a/∆
ii ) 1/r - 1/r²
= S/∆ - ( S - b )/∆
= ( S - S + b )/∆
= b/∆
iii ) 1/r - 1/r3
= S/∆ - ( S - c )/∆
= ( S - S + c )/∆
= c/∆
Now ,
LHS = (1/r-1/r1)(1/r-1/r2)(1/r-1/r3)
= ( a/∆ ) ( b/∆ ) ( c/∆ )
= ( abc )/∆³
= ( 4R * ∆ )/∆³
= 4R/∆²
= ( 4R )/( rs )² [ Since , ∆ = rs ]
= ( 4R )/( r²s² )
= RHS
•••••
Answered by
0
HELLO DEAR,
Answer:
Step-by-step explanation:
(1/r - 1/r1)( 1/r - 1/r2)(1/r - 1/r3)
=> {S/∆-(S-a)/∆}{ S/∆ - ( S - b )/∆}{ S/∆ - ( S - c )/∆}
=> {(S - S+a)/∆}{(S - S + b )/∆}{(S - S + c )/∆}
=> (a/∆)(b/∆)(c/∆)
=> (abc)/∆³
=> ( 4R * ∆ )/∆³
=> 4R/∆²
=> ( 4R )/( rs )²
[ ∆ = rs ]
=> ( 4R )/( r²s² )
Hence, (1/r - 1/r1)( 1/r - 1/r2)(1/r - 1/r3) = (abc)/∆³ = (4R )/( r²s² )
I HOPE IT'S HELP YOU DEAR,
THANKS
Similar questions